USING INFLUENCE DIAGRAMS IN MULTIPLE CRITERIA DECISION MAKING TASKS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The paper presents investigation into the solution of multiple criteria decision making problems. Influence diagrams can be used as a formal model of decision making under risk.